Progress Report: Gender characterizing/profiling in WEFE public sector institutions in Uzbekistan. Scoping study to identify capacity and needs of emerging leaders (men, women, and youth) for strengthening WEFE nexus approach Uzbekistan - Namozov, Orifjan; Babajanova, Zukhra; Sin, Liliana; Djumanazarova, Aygul (2024)
This report suggests a Nexus Capacity Assessment to inform a baseline understanding of the current WEFE nexus capacity of relevant institutions and stakeholders. The key targeted stakeholders are the WEFE-related government ministries/departments; academic institutions; including women professionals within these institutions. The specific objective of the project is to conduct an assessment of emerging leadership (women, youth) in Uzbekistan WEFE nexus public institutions to provide evidence for the follow-up matching capacity development program(s).